Implementation of Wireless DataCommunicationon Unmanned Aerial Vehicles (UAV) Technology forDetecting Damage of Building Roof (Case Study:Campus Building Institute of Informatics andBusiness Darmajaya) - Parjuangan, Sabam (Prosiding International conference on Information Technology and Business (ICITB), 2017)
Standards of care in multi-story buildings become anecessity. The standard of care should apply to all parts of thebuilding. One of the most important storied buildings thatrequire maintenance is the roof of the building. The side of theroof is the topside of the building, this side function to protectthe building from rainwater, wind, and sun. The very importantpart of the roof is treated and applies to all types of buildings.Especially for a roofed building that is roofed, the problem in itsmaintenance is an examination of the roof itself. Side handling ofthe roof is difficult to handle by humans without any tools. Onehandling for the roof side is the detection of roof sidedamage. Darmajaya multi-story building includes a high risebuilding that has a roof. Thus, Darmajaya building has problemsin detecting roof damage. So far, it detects roof damage inthe Damajaya building just by looking at the wet part of theinside of the building. This method cannot prevent theoccurrence of roof leaks. Therefore, a tool is needed to detectdamage to the roof side of Darmajaya building. The required toolis Unmanned Aerial Vehicles (UAV). Benefits of a UAV witha wifi antenna for wireless data communications. Wirelesscommunication is used for communication and sending video tomobile stations. Station device moves as a medium for displayingstreaming video. Mobile station devices are used tocontrol UAVs. Mobile-based mobile stations to run UAV controlapplications. The UAV control application is used tocontrol UAVs and cameras. The UAV application is also used tocontrol the camera as a picture capture and video recording. Theresults of the video in the form of streaming video that real-timeas a detection of damage to the roof of the building. So, to detectthe damage to the roof, can use a UAV equipped wifi antennaand camera. The results of this study the use of UAVs to detect damage to the roof of a multi-story building.Â Keywords : Multi-Story Building, Roof, Unmanned AerialVehicles, Wireless, and Communication.